Readequação do programa de autocontrole (PAC) de um frigorífico localizado na região da comunidade dos municípios de Campo Mourão (COMCAM) - Kaust, Mariana Carolina de Azevedo (2016)
Health standards and major process controls are important to prevent disease and maintain high quality standards in the industry, especially those related to the food industry whose raw materials are of animal origin. Paraná is the leading exporter of beef in Brazil and for its products being accepted in a competitive market, the industry in Paraná state has undergone a series of adaptations. The main changes are in order of sanitary and quality, for legal requirements of Agriculture Defense Agency of Parana, which become mandatory for the deployment of Self-Control Programs in slaughterhouses/fridges. Deployments of self-control programs are now a primary tool for the control of manufacturing processes, Aimed at quality assurance and safety of food produced, therefore, from the approach point of view the problem, from the point of view of the objectives and the point of view technical procedures, aimed to perform the self-control program Readjustments in a fridge lacated in the area of the Community of Campo Mourao and Municipalities, planning to eliminate as non-conformities raised by the state supervision and help to achieve higher quality standards. To this it was necessary to perform first a diagnosis by means of a checklist in order to identify a reality of processes, equipment, procedures used by industry. As results of the study, all the documents that make up the self control program of the company, were reviewed, readjusted and updated. The employees received training on a value of self-control program, sanitary hygienic procedures, PPE and operational procedures.